Tantangan dan Peluang Blockchain di Era Digital dalam Bidang Keamanan Data dan Transaksi Digital - Felicia, Felicia; Elvilie, Elvilie; Calista, Calista; Chic, Sebastian Areen; Bilqisthi, Muhammad Fardian; Joosten, Joosten (Journal of Comprehensive Science, 2024)
The digital era has changed the way we interact, conduct transactions, and store data. However, the security challenges related to data and transactions are now becoming more pressing. Cybercrime becoming increasingly sophisticated threatens the integrity and trust in digital systems. Blockchain technology, which is decentralized and records transactions permanently and transparently, has emerged as a promising solution. This article will discuss the potential of blockchain in enhancing data and transaction security in the future. We will review how blockchain builds a secure system with distributed and encrypted data, making it difficult to alter or hack. This technology supports verified and tamper-proof transactions, which in turn reduces the risk of fraud and increases trust in the financial system. Blockchain is considered an important step in protecting digital infrastructure and sensitive information. With features of decentralization, transparency, and strong cryptography, blockchain offers a high level of security that is difficult to manipulate. This article reviews the potential of blockchain in enhancing data and transaction security, as well as the challenges that need to be addressed. It was found that blockchain provides high-level security through decentralization, transparency, and strong cryptography. In addition, blockchain offers efficiency, automation through smart contracts, and the potential for widespread application across various sectors. Although there are limitations and challenges, collaborative efforts and continuous innovation can strengthen the role of blockchain in securing data and transactions in the future. It is hoped that this article provides a deeper understanding of the role of blockchain in addressing current and future digital security challenges, as well as how this technology can help create a safer and more trustworthy digital environment.